Um Novo Horizonte de Correlação para o Triássico Superior do Rio Grande do Sul - RUBERT, ROGÉRIO ROQUE; SCHULTZ, CESAR LEANDRO (Pesquisas em Geociências, 2004)
<!– .p text-align: justify; –> A new biozone - called Ictidosaur Assemblage Zone - is proposed to the Upper Triassic Caturrita Formation from Southern Brazil, based on the discovery of a distinct tetrapod association characterized by the presence of little non-mammalian cinodonts including Riograndia guaibensis, Brasilodon quadrangularis and Brasilitherium riograndensis. Besides, the advanced procolophonid Soturnia caliodon, the dinosaur Guaibasaurus candelariensis, the dicynodont Jachaleria candelariensis, indeterminated phytosaurs and sphenodontids were also found in this association. The new biozone overlies the Rhynchosaur Assemblage Zone and encloses the “Jachaleria Level” usually cited for these layers. Stratigraphical sections, as well as facies analysis, facies associations and architectural elements confirms that the new biozone is clearly included in a distinct stratigraphical level, which reflects a marked change in the fluvial pattern of the sequence. The anastomosed/meandering pattern associated to the underlying Rhynchosaur Assemblage Zone turns to a braided to low confinement fluvial system with unconfined flows. The faunal and faciological changes may have been caused by a combined action of climatic, base level and floral changes, probably reflecting the global tendency to an increasing aridity towards the end of the Triassic. It is presumed an early Norian age for the new biozone on basis on its faunal content, on its stratigraphic placement, recovering the Carnian rhynchosaur assemblage and also on the presence of woods, leafs and reproductive structures of conifers, whose morphological pattern is exclusively Triassic.